Presença familiar como mecanismo de governança corporativa : uma investigação da qualidade das informações contábeis nas empresas listadas no segmento tradicional da BM&BOVESPA - Grillo, Flávia Fardin (2015)
A familiar presence can be considered a corporate governance mechanism, since it exercises the monitoring of managers, reduces information asymmetry and also contributes to the financial statements are of better quality for businesses and users (Wang, 2006). Therefore, this study aimed to evaluate the effect of family presence on the quality of accounting information of Brazilian companies listed in the traditional segment of the BM&FBOVESPA, isolating the effect of other governance features present in other segments. The analysis of the effect of family presence considered aspects of ownership, control, management and board of directors. Four characteristics were addressed: informativeness, relevance, timeliness and conservatism, applying the model of the profits of Easton and Harris (1991) for informativeness, the value relevance model of Ohlson (1995), timiliness as shown by Lopes (2009) and conservatism according to Basu (1997). The sample comprises companies listed in the traditional segment of the BM & FBOVESPA in the period from 2010 to 2013. The results indicate that family property impacts negatively in the relevance of accounting information and earnings informativeness. Companies that have family members on the board or as CEO showed less relevant profit and greater relevance of equity. The founder of presence as CEO favored the relevance of the accounting profit. Regarding the influence of family presence in timing, it was found that the persistence of profits may suffer with the familiar presence in control and as president of the council. In contrast, family participation in the property contributes to the persistence of the profits, while the presence of family members on the board, as well as the founder, collaborates for the market in due course recognize profits. The presence of a family member, other than the founder as CEO, negatively impacts the recognition of contemporary time earnings by the market. Regarding the conditional conservatism, it notes that the family participation in control contributes positively to the company to adopt conservative positions while the familiar presence on the property and on the board, impacting negatively. It was also found that the companies controlled by the founding family are less conservative.